Ang hidden curriculum at edukasyon sa pagpapahalaga perspektibo mula sa antropolohiya - Abuso, Julian Elloso (Education quarterly.)
This essay elaborates the hidden curriculum is a cultural process that influences values formation among students. Because teachers serve as models, the paper argues that they ought to demonstrate through examples the values they transmit to their students.